KUALITAS BATA BETON BERLUBANG DENGAN BAHAN LIMBAH TAILING PENAMBANGAN EMAS UPBE PONGKOR - Amalia Amalia; Agus Murdiyoto (Politeknik Negeri Jakarta, 2019)
ABSTRACTThis study aims to investigate the potential of gold mining tailings UPBE Pongkor as hollow concrete brick making material and investigate its properties. The study was conducted by making hollow concrete brick composition 1 PC: 8 aggregate, consisting of 4 variations of tailings as aggregate substitution, ie 0%, 25%, 50%, and 75% of the aggregate weight. The results showed that (1) the use of tailings as aggregate replacement in concrete hollow brick can reduce the compressive strength of concrete blocks, (2) can be used as a substitute Tailings aggregate up to 75%, wherein the composition produces hollow concrete bricks that still meets ISO standards for class IV concrete brick that can be used as non-structural partition wall, (3) the higher levels replace sand tailings, water absorption in hollow concrete brick is also higher, (4) weight content of concrete hollow brick using more and more tailings, bulk density is decreased.Key words : Hollow concrete brick, compressive strength, tailing of gold mining